Mobilidade urbana sustentável: Conceitos, tendências e reflex\~oes - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The population mobility conditions are very degrading in Brazil in recent years with the increase in individual motorized transport, mainly due to the growth in traffic accidents with victims, urban congestion and also the vehicle pollutants. From this context, we tried to start a debate on the key attributes that characterize a model of sustainable urban mobility for Brazilian cities and what paths and principles to follow to make it viable. This paper presents some concepts on the subject, also discussing public policies necessary to make more sustainable mobility system from the point of view of concepts worked.
Keywords: R41; 330; sustainable transportation; mass transit; acessibility; smart growth; urban mobility